Fardes çunas y fadilas del guado y çala del madhab del çayd Abu Haniffa (B.U.B, ms. D.565): An Aljamiado-Morisco treatise for didactic religious purposes containing some novel linguistics features - Norri, Nezha (Anaquel de Estudios Árabes, 2018)
This article presents a synthesis of the third treatise in the manuscript Aljamiado D.565 at the University Library of Bologna. The text, entitled fardes çunas y fadilas del guado y çala del madhab del çayd Abu Haniffa, runs from folios 201 to 314. Through a series of chapters, the author of the treatise explains the conditions, rules and ordinances concerning ablution and prayer, according to the Hanafi school, founded by Abū Ḥanīfa an-Nucmān b. Tābit. This Aljamiado-Moorish text, which encompasses religious and moral themes, is undoubtedly due to the sociocultural atmosphere among the exiled Moriscos. Most authors of that period considered that addressing the lack of indoctrination of Moorish society was a religious duty, therefore their works took the form of an educational method directly inspired by the Quran the hadith literature. This review elaborates on the formal description, the content of this Aljamiado-Moorish text together with the sociolinguistic features characterizing its Aljamia.